KONSEP KHITBAH (PEMINANGAN) DALAM PERSPEKTIF HADIS RASULULLAH SAW - Ahmad Zuhri; Syukri Syukri; Tuti Handayani (UIN Sumatera Utara Medan, 2021)
Knowing the authenticity of hadith is indeed different from the Qur'an, because the bookkeeping of hadith was only carried out around the 3rd century Hijri. The time span is 200 years, and this is enough to provide opportunities for the possibility of diversity in hadith texts. By looking at this historical background, hadiresearch still needs to be done to fulfill the intellectual treasures of Muslims in understanding the basis of a problem through an understanding of the As-Sunnah. One of the hadiths that need to be reviewed, especially on the authentic side, is the hadith about proposals (Khitbah) in the Book of Sunan Abu Daud. Proposals in a marriage are highly recommended, but regarding the proposal process itself is very diverse, each region has a different proposal tradition, so the relevance of this hadith needs to be reviewed in order to get a more comprehensive meaning of the proposal process. For this research, the author tries to examine it by questioning several problems including what is meant by khitbah, how is the quality of the sanad and matan of the hadith and how the process of khitbah is in accordance with the sunnah or the rules of the Prophet Muhammad. The author uses the Madhu'i method. The object of this research is the prohibition of preaching on the proposal of others and the ability to look at the woman who is being preached. The results of this study explain that the quality of the hadith about the prohibition of proposing to someone else's proposal is Sahih and can be used as a hujjah (legal backing) and the quality of the hadith about the permissibility of looking at women who are preached initially is mauquf hasan but because there is a supporting hadith directly from the Prophet, the quality has increased to marfu' Sahih, because of that, the authenticity of this hadith is that it can be accepted and practiced.